The ownership structure and corporate performance based on Chinese stock market - LIU, Yanxuan (2017)
Abstract Purpose: This study researches the relationship between ownership structure and corporate performance of Chinese listed companies from 2012 to 2016. Methodology: This study uses the panel data for 1448 companies listed on the Chinese stock market. Results: Empirical analysis presents that proportion of fifth large shareholder has a significant positive association with performance of firm. In addition, for the ownership category, the fraction of legal person shares and proportion of tradable shares have the significant negative impact on business value. In some extent, the assets turnover ratio and the age of firm will boost the corporate performance. The size of firm and the debt to asset ratio have the significant negative impact on the business value. Conclusion: The Chinese listed companies should optimise the ownership structure, meanwhile, these companies should balance the debt to assets ratio, which reduces the financial risk.